Method for producing double-zero aluminum foil by using cast-rolling aluminum plate blank
By optimizing the composition and process of double zero aluminum foil, using high-efficiency multifunctional powder refining agent, argon-sulfur sulfhydryl carbon monoxide degassing and ultrasonic casting and rolling technology, the double zero aluminum foil is solved with insufficient strength, many pinholes and long process flow. Problem, improving production efficiency and finished product quality.
Patent Information
- Application Number
- CN202410997771.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing methods of producing double-zero aluminum foil using cast-rolled aluminum slabs have problems such as low strength, insufficient plasticity, many pinholes, long process flow and many processes, resulting in low production efficiency and high cost.
By scientifically designing the composition of double zero aluminum foil, using high-efficiency multifunctional powder refining agent for in-furnace spraying and refining, combining argon and sulfur hexafluoride carbon monoxide mixture, degassing online, using ceramic tube filtration and ultrasonic wave Auxiliary casting and rolling optimizes the cleanliness and uniformity of the aluminum alloy liquid and shortens the production process.
The strength, plasticity and yield of double-zero aluminum foil are significantly improved, the number of pinholes is reduced, the production cost is reduced, and an efficient production process is achieved.
Smart Images

Figure CN119120996A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum foil preparation technology, specifically relating to a method for producing double-zero aluminum foil using cast and rolled aluminum slabs. Background Technology
[0002] Double-zero aluminum foil is aluminum foil with a thickness of less than 0.01 mm. It possesses advantages such as a silvery-white luster, lightweight, softness, corrosion resistance, good thermal conductivity, and non-toxicity and odorlessness. As a moisture-proof, airtight, and light-shielding protective and packaging material, it is widely used in the food, pharmaceutical, beverage, cigarette, electronics, and electrical appliance industries. For example, it is used to package oils, meats, seafood, vegetables, and other food items to prevent oxidation and preserve freshness. It is also used as a covering material for circuit boards to protect them from electromagnetic interference and temperature rise. Furthermore, it is used as electrodes in electronic devices such as capacitors, inductors, and electrolytic capacitors.
[0003] In the early stages, double-zero aluminum foil was mainly produced using hot rolling technology. This involved casting molten aluminum into ingots, which were then milled on both sides and heated before undergoing multiple hot and cold rolling passes, with annealing interspersed throughout. This process resulted in a long process flow, numerous steps, high energy consumption, and low efficiency in the hot rolling production of double-zero aluminum foil.
[0004] Chinese patent document CN102728614A discloses a method for producing ultra-wide and ultra-thin aluminum foil casting billets by direct casting and rolling of electrolytic aluminum liquid. The method includes melting raw materials, performing electromagnetic stirring 2 to 3 times, refining by injecting carbon tetrachloride, adding solid aluminum ingots or intermediate alloys or waste to adjust the composition, refining again, settling, filtering, online hydrogen removal, filtering again, grain refinement, and casting and rolling.
[0005] Chinese patent document CN117626020A discloses a method for producing aluminum foil casting billets for power batteries, including melting molten aluminum, refining in a smelting furnace three times, turning the furnace over, refining in a holding furnace three times, online degassing and filtration, grain refinement and vibration using an ultrasonic device, casting and rolling, and finally coiling to obtain aluminum foil casting billets for power batteries.
[0006] Chinese patent document CN117089735A discloses a method for preparing 8079 double-zero aluminum foil blanks using electrolytic aluminum liquid, including screening qualified electrolytic aluminum liquid, vacuum ladle powder spraying refining, vacuum ladle batching, adjusting the aluminum liquid composition in the melting furnace, refining in the melting furnace, refining in the static furnace, online grain refinement, degassing in the degassing box, double filtration by connecting foam ceramic filter plate and ceramic filter tube in series, treatment, casting and rolling, annealing and cold rolling.
[0007] Chinese patent document CN108300911A discloses a method for producing 8111 alloy aluminum foil from cast and rolled billets, which includes, in sequence, furnace loading, batching, powder spraying refining, first liquid refining, slag removal, furnace turning, second liquid refining, static filtration, casting and rolling, first cold rolling, homogenization annealing, second cold rolling, rewinding and intermediate trimming, third cold rolling, intermediate annealing, fourth cold rolling, rewinding and finished product trimming, inspection, and finished product packaging.
[0008] The production of double-zero aluminum foil requires extremely high cleanliness and uniformity of microstructure in the aluminum slab. Based on literature review and practical experience, existing technologies for producing double-zero aluminum foil using cast-rolled aluminum slabs still have the following problems: (1) Double-zero aluminum foil generally suffers from low strength, insufficient plasticity, or excessive pinholes, failing to meet usage requirements and resulting in a low yield. (2) The production process still involves a long process flow and numerous steps. To obtain high-cleanliness aluminum liquid that meets the requirements of double-zero aluminum foil, multiple powder spraying refining and online degassing filtration processes are usually required, increasing production steps and exacerbating oxidation and burn-off of the aluminum liquid, leading to increased production costs. Therefore, existing methods for producing double-zero aluminum foil using cast-rolled aluminum slabs still need improvement and development. Summary of the Invention
[0009] To address the problems and shortcomings mentioned in the background art, this invention provides a method for producing double-zero aluminum foil using cast-rolled aluminum slabs. By scientifically designing the composition of the double-zero aluminum foil, optimizing the degassing and slag removal process of the aluminum alloy melt, and employing high-energy ultrasonic-assisted casting-rolling of the aluminum slab, the cleanliness and uniformity of the microstructure of the cast-rolled aluminum slab are improved, enabling the casting-rolling production of double-zero aluminum foil, shortening the production process, improving the strength and plasticity of the double-zero aluminum foil, reducing the number of pinholes, and solving the problems and shortcomings mentioned in the background art.
[0010] The technical solution adopted by the present invention to achieve the above objectives is as follows:
[0011] The first aspect of the present invention provides a double-zero aluminum foil, characterized in that the double-zero aluminum foil is composed of the following components in mass percentage: Si 0.1-0.3%, Fe 0.5-0.9%, Zn≤0.1%, Cu≤0.05%, Mn≤0.05%, Mg≤0.05%, V≤0.05%, with the balance being Al and other unavoidable impurities, wherein the content of each other impurity is ≤0.03% and the total amount of other impurities is ≤0.1%.
[0012] Si and Fe are the main alloying components of double-zero aluminum foil. Si and Fe have a solid solution strengthening effect in double-zero aluminum foil, enhancing its strength. Insufficient Si and Fe content leads to insufficient strength. Higher Si and Fe content results in higher strength. However, excessive Si and Fe content reduces the plasticity and corrosion resistance of the double-zero aluminum foil and produces coarse intermetallic compounds, causing pinholes and tears. Therefore, the Si and Fe content must be strictly limited. Zn, Cu, Mn, Mg, and V are all impurity elements in double-zero aluminum foil. While these impurity elements also enhance the strength of the foil, excessive content reduces its gloss, plasticity, and corrosion resistance, and can even cause pinholes and tears. Therefore, the content of these impurity elements must also be strictly limited.
[0013] A second aspect of the present invention provides a method for producing double-zero aluminum foil using cast-rolled aluminum slabs, characterized by comprising the following steps in sequence:
[0014] Step 1: Prepare the aluminum alloy liquid by melting and mixing according to the composition and mass percentage of the double-zero aluminum foil;
[0015] Step 2: The molten aluminum alloy in the furnace is subjected to spray refining treatment using argon gas and powdered refining agent to remove gas and impurities;
[0016] Step 3: The molten aluminum alloy is sequentially flowed through the degassing box and filter box set on the flow channel for online degassing and filtration treatment;
[0017] Step 4: Under the action of ultrasound, the molten aluminum alloy is continuously cast and rolled into aluminum sheet coil I;
[0018] Step 5: Perform a first cold rolling and high-temperature annealing on aluminum coil I to obtain aluminum coil II;
[0019] Step Six: Perform a second cold rolling and medium-temperature annealing on aluminum sheet coil II to obtain aluminum foil coil I;
[0020] Step 7: Perform a third cold rolling and low-temperature annealing on aluminum foil roll I to obtain aluminum foil roll II;
[0021] Step 8: Perform a fourth cold rolling and finished product annealing on aluminum foil roll II to obtain the double-zero aluminum foil.
[0022] Furthermore, the aluminum melting furnace used in step one for smelting and preparing the aluminum alloy liquid is a regenerative gas-fired aluminum melting furnace, with a heating and melting temperature of 720-740℃. Besides regenerative gas-fired aluminum melting furnaces, resistance furnaces or electromagnetic induction furnaces can also be used. Because regenerative gas-fired aluminum melting furnaces have the advantages of high efficiency and energy saving, which helps reduce production costs, they are preferred for smelting and preparing the aluminum alloy liquid. The heating and melting temperature should not be lower than 720℃, otherwise the melting speed of the aluminum ingots will be slow, affecting production efficiency. The heating and melting temperature should also not be higher than 740℃, otherwise it will aggravate the oxidation and burning loss of the aluminum ingots and aluminum alloy liquid, which will also increase production costs.
[0023] Furthermore, in step two, the purity of the argon gas is ≥99.99%, the amount of powder refining agent used is 0.1-0.2% of the weight of the aluminum alloy liquid, and the spraying refining time is 10-20 minutes.
[0024] The production of double-zero aluminum foil requires a high degree of cleanliness in the molten aluminum alloy. Pores and inclusions can cause defects such as pinholes, blistering, and tearing in the double-zero aluminum foil, reducing its strength, plasticity, and corrosion resistance. Therefore, the production of double-zero aluminum foil necessitates enhanced degassing and slag removal purification treatment of the molten aluminum alloy.
[0025] The spray refining process involves using a powder spraying can and metal pipe, employing argon gas as a carrier to spray powdered refining agent into the molten aluminum alloy. This allows the refining agent to fully contact and react with the molten aluminum alloy, subsequently carrying away inclusions and hydrogen from the molten aluminum alloy. The degassing and slag removal efficiency of the spray refining process is related to the purity of the argon gas, the amount of refining agent used, and the spray refining time. Higher argon purity results in a better spray refining effect, but also increases production costs. The spray refining time should not be too short, and the amount of refining agent used should not be too small, otherwise the degassing and slag removal effect will not be achieved. The spray refining time should also not be too long, otherwise it will increase the oxidation loss of the molten aluminum alloy. The amount of refining agent used should also not be too large, otherwise it will lead to excessive alkali metal content in the molten aluminum alloy. After the spray refining process is completed and the slag on the surface of the molten aluminum alloy is removed, a covering agent should be promptly applied to the surface of the molten aluminum alloy to prevent oxidation loss and re-absorption of gas.
[0026] Further, the powder refining agent described in step two is composed of the following components by mass percentage: NaCl 35.12%, NaF 19.84%, TiCl3 16.51%, SrSO4 10.06%, KPO3 11.45%, Na2B4O7 7.02%. The preparation method of the powder refining agent includes the following steps in sequence:
[0027] (1) According to the composition and mass percentage of the refining agent, select NaCl, NaF, TiCl3, SrSO4, KPO3 and Na2B4O7 with a purity ≥99.8% as raw materials for formulation; (2) Add the ingredients to water at 70°C and stir to dissolve into an aqueous solution. The mass ratio of water to ingredients is 1.2. Then heat to 100°C to evaporate the aqueous solution to obtain solid crystals; (3) Crush the solid crystals into powder with a particle size of less than 2 mm. Dry the powder at 160°C for 4 hours to obtain the refining agent.
[0028] The degassing and slag removal efficiency of spray refining is closely related to the composition and preparation method of the refining agent. Existing refining agents are mainly composed of fluoride and chloride salts, obtained by direct mixing after crushing. The components of the refining agent exist independently, resulting in a high melting point and low degassing and impurity removal efficiency. To obtain highly clean aluminum alloy liquid, the refining agent must be sprayed multiple times, which not only increases the production process but also significantly increases the oxidation and burn-off of the aluminum alloy liquid, leading to excessive alkali metals in the aluminum alloy liquid and reducing the surface gloss, mechanical properties, and corrosion resistance of double-zero aluminum foil. Furthermore, existing refining agents have limited functionality and lack refining and modifying functions, requiring separate addition of refining and modifying agents, thus increasing the production process and cost of double-zero aluminum foil.
[0029] To address the problems and shortcomings of existing refining agents, this invention develops a highly efficient, multifunctional powder refining agent for the production of double-zero aluminum foil. The refining agent is prepared using a solution evaporation method. Through solution evaporation, the components recrystallize to form a eutectic with a lower melting point. For example, NaCl typically has a melting point of 801℃, and NaF typically has a melting point of 993℃. When they form a NaCl·NaF eutectic, the melting point drops to 698℃, significantly reducing the refining agent's melting point and making it easier to dissolve in molten aluminum alloy, thus enhancing its degassing and slag-removing effects. Specifically, NaCl reacts with the molten aluminum alloy to generate AlCl3, which has a boiling point of only 180℃. As AlCl3 bubbles rise, they adsorb and capture impurities and hydrogen gas, escaping from the molten aluminum alloy and thus achieving degassing and slag removal. NaF molten salt can break down the alumina film, allowing inclusions such as alumina to dissolve into the molten salt. This increases the surface tension between the inclusions and the molten aluminum alloy, promoting their separation and enhancing the slag removal function of the refining agent. The Ti element generated from the reaction of TiCl3 with the molten aluminum alloy directly enters the molten aluminum alloy, refining the grains of the cast and rolled aluminum slab, improving its plasticity and uniformity of microstructure, and avoiding the need for additional refining agents that would increase production costs. The generated AlCl3 bubbles can also adsorb and capture inclusions and hydrogen in the molten aluminum alloy during their ascent, enhancing the degassing and slag removal effect of the refining agent. The Sr and P elements generated from the reaction of SrSO4 and KPO3 with the molten aluminum alloy enter the molten aluminum alloy, refining the modified Si phase, improving the strength and plasticity of the double-zero aluminum foil, and eliminating pinhole and tearing defects caused by coarse Si phases. The SO2 bubbles obtained from the reaction can also adsorb and capture inclusions and hydrogen in the molten aluminum alloy during their ascent, enhancing the degassing and slag removal capabilities of the refining agent. Na2B4O7 reacts with molten aluminum alloy to generate boron, which enters the molten aluminum alloy. This can refine the modified Fe-rich phase, improve the strength and plasticity of double-zero aluminum foil, and eliminate pinhole and tearing defects caused by coarse Fe-rich phase.
[0030] Furthermore, the degassing medium introduced into the degassing box in step three is a mixed gas composed of argon, sulfur hexafluoride and carbon monoxide with a purity of ≥99.99%, wherein the volume percentage of sulfur hexafluoride in the mixed gas is 9-11% and the volume percentage of carbon monoxide is 3-5%.
[0031] After in-furnace refining with in-furnace refining agent, the gas and slag content of the aluminum alloy molten metal is significantly reduced. However, the molten metal still contains gas and slag because the refining agent refining process introduces inclusions such as chloride and fluoride salts. Furthermore, while refining agent refining also has a dehydrogenation effect, its effectiveness is limited. This is because the refining agent inevitably contains moisture, which is introduced during refining, causing the aluminum alloy molten metal to reabsorb hydrogen. This means that dehydrogenation during refining is always in a dynamic equilibrium, and it is typically difficult to reduce the hydrogen content of the aluminum alloy molten metal to below 0.1 ml / 100g Al. Therefore, to obtain highly clean aluminum alloy molten metal, external online degassing and filtration treatment is also necessary.
[0032] In existing degassing chamber technologies, the degassing medium introduced into the chamber is typically an inert gas such as nitrogen or argon, or a mixture of an inert gas and chlorine. Because nitrogen, argon, and chlorine have small relative molecular masses and low densities (nitrogen has a relative molecular mass of 28.01 and a density of 1.25 kg / m³), this degassing process is highly efficient. 3 Argon has a relative molecular mass of 39.94 and a density of 1.78 kg / m³. 3 Chlorine gas has a relative molecular mass of 70.91 and a density of 3.21 kg / m³. 3 This results in bubbles rising too quickly in the molten aluminum alloy, and the contact time between the bubbles and the molten aluminum alloy is too short, which greatly affects the degassing effect of the degassing box. Furthermore, although chlorine has a relatively high density, it is a toxic gas with a strong, pungent odor, which not only severely corrodes equipment but also causes environmental pollution.
[0033] To address the problems and shortcomings of existing degassing box technologies and improve their degassing efficiency, this invention introduces a mixed gas consisting of argon (≥99.99% purity), sulfur hexafluoride (SF6), and carbon monoxide as the degassing medium. SF6 is a high-density, highly stable gas that is non-toxic, non-flammable, and non-corrosive. It has a relative molecular mass of 146.05 and a density of 6.5 kg / m³. 3 Adding 9-11% sulfur hexafluoride by volume to the mixed gas can significantly slow down the rising speed of bubbles in the molten aluminum alloy, increase the contact time between the bubbles and the molten aluminum alloy, and enable the bubbles to capture and adsorb more hydrogen and inclusions, thereby improving the degassing effect of the degassing box. Adding 3-5% carbon monoxide by volume to the mixed gas aims to allow the carbon monoxide to capture oxygen in the molten aluminum alloy, forming carbon dioxide. This prevents oxygen from reacting with aluminum to form an alumina film on the bubble surface, enhancing the bubbles' ability to capture and adsorb hydrogen and inclusions, and improving the degassing effect. Through mixed gas refining, the hydrogen content of the molten aluminum alloy can be reduced to below 0.1 ml / 100g Al, significantly improving the cleanliness of the molten aluminum alloy.
[0034] Furthermore, in step three, the graphite rotor in the degassing box rotates at 400-500 rpm, the flow rate of the mixed gas is 4-5 cubic meters per hour, and the pressure of the mixed gas is 0.2-0.3 MPa.
[0035] The degassing process in the degassing box involves passing molten aluminum alloy through it. A high-speed rotating graphite rotor inside the box shears and breaks the mixed gas into small, uniform bubbles. The partial pressure difference of hydrogen between the molten aluminum alloy and the bubbles causes hydrogen atoms in the molten aluminum alloy to continuously diffuse into the bubbles. The bubbles then float upwards along a spiral trajectory and escape from the molten aluminum alloy. The degassing effect of the degassing box is also related to the rotational speed of the graphite rotor, the flow rate of the mixed gas, and the pressure. The rotational speed of the graphite rotor cannot be too low, otherwise it will not be able to shear and break the bubbles; however, the rotational speed cannot be too high either, otherwise it will easily cause aluminum splashing. The flow rate of the mixed gas cannot be too low, and the pressure cannot be too low, otherwise the number of bubbles will be too small. However, the flow rate does not need to be too high, and the pressure does not need to be too high either, otherwise it will increase production costs and cause excessive splashing of the molten aluminum alloy.
[0036] Furthermore, the filter box mentioned in step three is a tubular filter box. The filter medium in the tubular filter box is a ceramic filter tube, which is made by high-temperature sintering of fine silicon nitride ceramic particles with a binder. It has numerous tortuous pores inside. When the molten aluminum alloy flows through the ceramic filter tube, impurities are adsorbed or blocked on the surface and inner walls of the pores, achieving filtration and impurity removal. The ceramic filter tube has high thermal strength, strong resistance to thermal shock and erosion, large filtration capacity, and high filtration efficiency. The structure and usage of the tubular filter box are available in publicly available literature and will not be elaborated here. Tubular filtration is a high-precision filtration method; after tubular filtration, the removal rate of impurities larger than 5μm in the molten aluminum alloy can reach over 98%, and the slag content in the molten aluminum alloy can be reduced to 0.05mm. 2 / kg, thereby significantly improving the cleanliness of the aluminum alloy liquid, avoiding the presence of inclusions that could cause defects such as pinholes and tears in the double-zero aluminum foil, and improving the strength, plasticity and corrosion resistance of the double-zero aluminum foil.
[0037] Furthermore, in step four, the frequency of the ultrasonic wave is 30-40kHz, the power of the ultrasonic wave is 10-15kW, the temperature of the aluminum alloy melt is 690-700℃, the casting and rolling speed is 800-900 mm / min, and the thickness of aluminum plate coil I is 6-8 mm.
[0038] Double-zero aluminum foil requires high uniformity of microstructure and composition in the cast-rolled aluminum slab. Coarse grains and uneven composition in the slab can lead to defects such as tearing, color difference, and mottling in the double-zero aluminum foil. Casting involves injecting molten aluminum alloy directly into the gap between the two rolls of a casting mill through a front-box nozzle. The molten aluminum then cools and solidifies into an aluminum slab under the cooling and pressure of the rolls. Under conventional casting conditions, the non-equilibrium solidification of the molten aluminum alloy results in coarse grains in the cast-rolled aluminum slab, causing compositional segregation across the cross-section and leading to uneven microstructure and an inability to meet the production requirements of double-zero aluminum foil.
[0039] To address the problems and shortcomings of conventional casting and rolling processes, this invention employs ultrasonic wave-assisted casting and rolling. The ultrasonic probe is placed in the molten aluminum alloy in the front chamber of the casting and rolling mill. Through ultrasonic vibration and acoustic cavitation effects, the temperature uniformity of the molten aluminum alloy in the casting and rolling zone is improved, increasing the number of heterogeneous grain nucleations and preventing compositional segregation in the molten aluminum alloy. This effectively refines the grains of the cast-rolled aluminum slab and improves its compositional uniformity. To effectively utilize the ultrasonic waves and meet the requirements of double-zero aluminum foil for the cast-rolled aluminum slab, the ultrasonic frequency must not be lower than 30kHz, and the ultrasonic power must not be lower than 10kW; otherwise, a sufficiently fine grain and sufficiently uniform composition cannot be obtained. Furthermore, the thickness of the aluminum slab must not be less than 6 mm; otherwise, sufficient deformation cannot be achieved during the subsequent double-zero aluminum foil rolling process. However, the thickness of the aluminum slab cannot be too thick, otherwise, it will increase the number of subsequent cold rolling and annealing cycles.
[0040] Furthermore, in step five, the high-temperature annealing temperature is 560-570℃, the annealing time is 12-14 hours, and the thickness of the aluminum plate coil II is 3-4 mm.
[0041] Furthermore, in step six, the temperature of the medium-temperature annealing is 420-430℃, the annealing time is 10-12 hours, and the thickness of the aluminum foil roll I is 0.1-0.2 mm.
[0042] Furthermore, the low-temperature annealing temperature in step seven is 220-230℃, the annealing time is 5-6 hours, and the thickness of the aluminum foil roll II is 0.02-0.04 mm.
[0043] Furthermore, in step eight, the annealing temperature of the finished product is 180-190℃, the annealing time is 3-4 hours, and the thickness of the double-zero aluminum foil is 0.005-0.009 mm.
[0044] Cast-rolled aluminum slabs must undergo multiple cold rolling and annealing passes to obtain the final double-zero aluminum foil. Controlling the cold rolling and annealing processes is crucial for obtaining high-quality double-zero aluminum foil. This requires rationally allocating the deformation amount in each cold rolling pass, including the first, second, third, and fourth cold rolling passes, while strictly controlling the annealing temperatures for high-temperature annealing, medium-temperature annealing, low-temperature annealing, and final annealing. Improper deformation amounts and annealing temperatures in each cold rolling pass can lead to cracking of the aluminum sheet and foil coils, preventing the production of high-quality, high-performance double-zero aluminum foil.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) This invention significantly reduces the gas and slag content of molten aluminum alloy by employing a highly efficient and multifunctional recrystallized powder refining agent for in-furnace blowing refining, online degassing in a mixed gas degassing box, and ceramic tube filtration. This reduces the hydrogen content of the molten aluminum alloy to below 0.1 ml / 100gAl and the inclusion content to 0.05 mm. 2 By significantly improving the cleanliness of the aluminum alloy liquid, the harmful effects of porosity and inclusions on the mechanical properties of double-zero aluminum foil are eliminated, the strength and plasticity of double-zero aluminum foil are improved, and defects such as pinholes, bubbles, and tears caused by porosity and inclusions are avoided, thus improving the yield of double-zero aluminum foil.
[0047] (2) This invention solves the problems of low strength, insufficient plasticity and excessive pinholes that are common in the production of double-zero aluminum foil from existing rolled aluminum slabs. The produced double-zero aluminum foil has a tensile strength of over 100 MPa, an elongation after fracture of over 5%, and a pinhole count of less than 50 per square meter. It has the advantages of high strength, good ductility and low pinhole count.
[0048] (3) The present invention significantly shortens the production process of double zero aluminum foil, reduces production steps, improves the production efficiency of double zero aluminum foil, and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a process flow diagram of the present invention for producing double-zero aluminum foil using cast and rolled aluminum slabs. Detailed Implementation
[0050] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0051] Example 1:
[0052] Double-zero aluminum foil is composed of the following components by mass percentage: Si 0.19%, Fe 0.72%, Zn 0.07%, Cu 0.01%, Mn 0.02%, Mg 0.03%, V 0.01%, with the balance being Al and other unavoidable impurities, with each individual impurity ≤0.03% and the total amount of other impurities ≤0.1%. The production method includes the following steps: Step 1: Prepare molten aluminum alloy at 730℃ using a regenerative gas-fired aluminum melting furnace, according to the composition and mass percentage of the double-zero aluminum foil; Step 2: Degas and remove impurities from the molten aluminum alloy by spraying it with 99.99% pure argon and 0.15% (by weight) powdered refining agent from the molten aluminum alloy for 15 minutes; Step 3: Flow the molten aluminum alloy sequentially through a degassing box and a tubular filter box located on the flow channel for online degassing and filtration. The degassing medium introduced into the degassing box is a mixture of 99.99% pure argon, sulfur hexafluoride, and carbon monoxide. The volume percentage of sulfur hexafluoride in the mixture is 10%, and the volume percentage of carbon monoxide is 4%. The graphite rotor in the degassing box rotates at 450 rpm, and the flow rate of the mixture is 4.5 cubic meters. Step 4: Under the action of ultrasonic waves with a frequency of 35kHz and a power of 12.5kW, the aluminum alloy liquid at 695℃ is continuously cast and rolled into an aluminum sheet coil I with a diameter of 7 mm at a casting and rolling speed of 850 mm / min; Step 5: The aluminum sheet coil I is subjected to a first cold rolling and annealed at 565℃ for 13 hours to obtain an aluminum sheet coil II with a diameter of 3.5 mm; Step 6: The aluminum sheet coil II is subjected to a second cold rolling and annealed at 425℃ for 11 hours to obtain an aluminum foil coil I with a diameter of 0.15 mm; Step 7: The aluminum foil coil I is subjected to a third cold rolling and annealed at 225℃ for 5.5 hours to obtain an aluminum foil coil II with a diameter of 0.03 mm; Step 8: The aluminum foil coil II is subjected to a fourth cold rolling and annealed at 185℃ for 3.5 hours to obtain a double-zero aluminum foil with a thickness of 0.007 mm.
[0053] Example 2:
[0054] The double-zero aluminum foil is composed of the following components by mass percentage: Si 0.1%, Fe 0.9%, Zn 0.02%, Cu 0.02%, Mn 0.01%, Mg 0.02%, V 0.01%, with the balance being Al and other unavoidable impurities, the individual content of which is ≤0.03% and the total amount of which is ≤0.1%. The production method includes the following steps: Step 1: Prepare molten aluminum alloy at 740℃ using a regenerative gas-fired aluminum melting furnace, according to the composition and mass percentage of the double-zero aluminum foil; Step 2: Degas and remove impurities from the molten aluminum alloy by spraying it with 99.99% pure argon and 0.2% (by weight) powdered refining agent from the molten aluminum alloy for 20 minutes; Step 3: Flow the molten aluminum alloy sequentially through a degassing box and a tubular filter box located on the flow channel for online degassing and filtration. The degassing medium introduced into the degassing box is a mixture of 99.99% pure argon, sulfur hexafluoride, and carbon monoxide. The volume percentage of sulfur hexafluoride in the mixture is 9%, and the volume percentage of carbon monoxide is 5%. The rotation speed of the graphite rotor in the degassing box is 500 rpm, and the flow rate of the mixture is... Step 4: Under the action of ultrasonic waves with a frequency of 40kHz and a power of 10kW, the molten aluminum alloy at 700℃ is continuously cast and rolled into 6 mm aluminum sheet coil I at a casting and rolling speed of 900 mm / min; Step 5: The aluminum sheet coil I is subjected to a first cold rolling and annealed at 570℃ for 12 hours to obtain 3 mm aluminum sheet coil II; Step 6: The aluminum sheet coil II is subjected to a second cold rolling and annealed at 430℃ for 10 hours to obtain 0.1 mm aluminum foil coil I; Step 7: The aluminum foil coil I is subjected to a third cold rolling and annealed at 230℃ for 5 hours to obtain 0.02 mm aluminum foil coil II; Step 8: The aluminum foil coil II is subjected to a fourth cold rolling and annealed at 180℃ for 4 hours to obtain a double-zero aluminum foil with a thickness of 0.005 mm.
[0055] Example 3:
[0056] The double-zero aluminum foil is composed of the following components by mass percentage: Si 0.3%, Fe 0.5%, Zn 0.01%, Cu 0.01%, Mn 0.02%, Mg 0.02%, V 0.01%, with the balance being Al and other unavoidable impurities, the individual content of which is ≤0.03% and the total amount of other impurities is ≤0.1%. The production method includes the following steps in sequence: Step 1: Prepare aluminum alloy liquid by melting and mixing in a regenerative gas-fired aluminum melting furnace at 720℃ according to the composition and mass percentage of double-zero aluminum foil; Step 2: Degas and remove impurities from the aluminum alloy liquid by spraying it with 99.99% pure argon gas and 0.1% powdered refining agent by weight of the aluminum alloy liquid for 10 minutes; Step 3: Flow the aluminum alloy liquid sequentially through a degassing box and a tubular filter box set on the flow channel for online degassing and filtration. The degassing medium introduced into the degassing box is a mixed gas composed of 99.99% pure argon gas, sulfur hexafluoride, and carbon monoxide. The volume percentage of sulfur hexafluoride in the mixed gas is 11%, and the volume percentage of carbon monoxide is 3%. The rotation speed of the graphite rotor in the degassing box is 400 rpm, and the flow rate of the mixed gas is... The flow rate is 5 cubic meters per hour, and the pressure of the mixed gas is 0.2 MPa; Step 4: Under the action of ultrasonic waves with a frequency of 30 kHz and a power of 15 kW, the molten aluminum alloy at 690°C is continuously cast and rolled into an 8 mm aluminum sheet coil I at a casting and rolling speed of 800 mm / min; Step 5: The aluminum sheet coil I is subjected to a first cold rolling and annealed at 560°C for 14 hours to obtain an 4 mm aluminum sheet coil II; Step 6: The aluminum sheet coil II is subjected to a second cold rolling and annealed at 420°C for 12 hours to obtain an 0.2 mm aluminum foil coil I; Step 7: The aluminum foil coil I is subjected to a third cold rolling and annealed at 220°C for 6 hours to obtain an 0.04 mm aluminum foil coil II; Step 8: The aluminum foil coil II is subjected to a fourth cold rolling and annealed at 190°C for 3 hours to obtain a double-zero aluminum foil with a thickness of 0.009 mm.
[0057] The powder refining agent described in Examples 1-3 of this invention is composed of the following components by mass percentage: NaCl 35.12%, NaF 19.84%, TiCl3 16.51%, SrSO4 10.06%, KPO3 11.45%, and Na2B4O7 7.02%. The preparation method of the refining agent includes the following steps in sequence: (1) According to the composition and mass percentage of the refining agent, select NaCl, NaF, TiCl3, SrSO4, KPO3, and Na2B4O7 with a purity of 99.8% as raw materials for batching; (2) Add the batching to water at a temperature of 70°C and stir to dissolve it into an aqueous solution. The mass ratio of water to batching is 1.2. Then heat to 100°C to evaporate the aqueous solution to obtain a solid crystal; (3) Crush the solid crystal into powder with a particle size of less than 2 mm, and dry the powder at 160°C for 4 hours to obtain the powder refining agent.
[0058] Comparative Example 1:
[0059] The production method of the comparative example double-zero aluminum foil is the same as that of Example 1, except that the double-zero aluminum foil is composed of the following components by mass percentage: Si 0.19%, Fe 0.45%, Zn 0.07%, Cu 0.01%, Mn 0.02%, Mg 0.03%, V 0.01%, with the balance being Al and other unavoidable impurities, the content of each other impurity being ≤0.03%, and the total amount of other impurities being ≤0.1%.
[0060] Comparative Example 2:
[0061] The composition, mass percentage, and production method of the comparative example double-zero aluminum foil are the same as those of Example 1. The difference is that the powder refining agent used is a commercially available conventional powder refining agent, which consists of the following components in mass percentage: NaCl 36.13%, KCl 15.42%, CaF2 16.84%, NaF 19.24%, C2Cl6 12.37%. This powder refining agent is obtained by directly crushing and mixing the raw materials.
[0062] Comparative Example 3:
[0063] The composition, mass percentage, and production method of the comparative example double-zero aluminum foil are the same as those of Example 1. The difference is that the degassing medium introduced into the degassing box in step three is argon gas with a purity of 99.99%, instead of a mixture of argon gas with a purity of 99.99%, sulfur hexafluoride, and carbon monoxide.
[0064] Comparative Example 4:
[0065] The composition, mass percentage, and production method of the comparative example double-zero aluminum foil are the same as those of Example 1. The difference is that ultrasonic waves were not used in step four, but the aluminum alloy liquid was continuously cast and rolled into aluminum sheet coils under conventional conditions.
[0066] Verification Example 1:
[0067] The hydrogen content and slag content of the aluminum alloy melts before continuous casting and rolling in Examples 1-3 and Comparative Examples 2-3 were measured on-site using an HDA-V hydrogen analyzer and an Analyze PoDFA slag analyzer. The results are shown in Table 1. Table 1 shows that the hydrogen content of the aluminum alloy melts in Examples 1-3 was less than 0.1 ml / 100 g Al, and the slag content was less than 0.05 mm. 2 / kgAl. Comparative Example 2, due to the use of commercially available conventional refining agents, resulted in relatively high gas and slag content in the molten aluminum alloy. Comparative Example 3, because the degassing medium introduced into the degassing box was only argon, without the use of a mixed gas, also resulted in relatively high gas and slag content in the molten aluminum alloy. The comparison shows that the technical solution of this invention can significantly reduce the gas and slag content of the molten aluminum alloy before casting and rolling, and improve the cleanliness of the cast and rolled aluminum slab and the final double-zero aluminum foil.
[0068] Table 1 Hydrogen content and slag content of aluminum alloy melt
[0069] Hydrogen content (ml / 100gAl) <![CDATA[Sludge content / (mm 2 / kg Al)]]> Example 1 0.072 0.038 Example 2 0.055 0.024 Example 3 0.091 0.041 Comparative Example 2 0.118 0.092 Comparative Example 3 0.164 0.073
[0070] Verification Example 2:
[0071] Samples were taken from the double-zero aluminum foils obtained in Examples 1-3 and Comparative Examples 1-4, and the tensile strength and elongation after fracture of the double-zero aluminum foils were tested. The results are shown in Table 2. Table 2 shows that the tensile strength of the double-zero aluminum foils in Examples 1-3 is greater than 100 MPa, and the elongation after fracture is greater than 5%. In Comparative Example 1, the insufficient Fe content resulted in a tensile strength of less than 100 MPa for the double-zero aluminum foil. Comparative Example 2, due to the use of commercially available conventional powder refining agents for in-furnace blowing refining; Comparative Example 3, due to the lack of online degassing in the degassing box using mixed gas; and Comparative Example 4, due to the lack of continuous casting and rolling under ultrasonic action, all resulted in tensile strengths of double-zero aluminum foils of Comparative Examples 2-4 being less than 100 MPa and elongation after fracture less than 5%. The comparison shows that the technical solution of this invention can significantly improve the strength and plasticity of double-zero aluminum foil.
[0072] Table 2 Tensile strength and elongation after fracture of double-zero aluminum foil
[0073] Tensile strength / MPa Elongation after fracture / % Example 1 118.4 6.9 Example 2 126.3 5.2 Example 3 102.9 5.8 Comparative Example 1 91.7 7.1 Comparative Example 2 85.6 3.8 Comparative Example 3 88.5 4.5 Comparative Example 4 95.6 4.7
[0074] Verification Example 3:
[0075] Samples were taken from the double-zero aluminum foils obtained in Examples 1-3 and Comparative Examples 1-4, and the average number of pinholes per square meter of double-zero aluminum foil was measured. The results are shown in Table 3. Table 3 shows that the average number of pinholes in the double-zero aluminum foils of Examples 1-3 and Comparative Example 1 is less than 50 pinholes / square meter. Comparative Example 2, due to the use of commercially available conventional powder refining agents for in-furnace blowing refining, Comparative Example 3, due to the lack of online degassing in the degassing box using mixed gas, and Comparative Example 4, due to the lack of continuous casting and rolling under ultrasonic action, resulted in an average number of pinholes greater than 100 pinholes / square meter for the double-zero aluminum foils of Comparative Examples 2-4. The comparison shows that the technical solution of this invention can significantly reduce the number of pinholes in double-zero aluminum foil.
[0076] Table 2 Average number of pinholes in double-zero aluminum foil
[0077] Average number of pinholes (per square meter) Example 1 42 Example 2 36 Example 3 49 Comparative Example 1 43 Comparative Example 2 126 Comparative Example 3 101 Comparative Example 4 109
Claims
1. A double zero aluminum foil, It is characterized in that The double-zero aluminum foil is composed of the following components in mass percentage: Si 0.1-0.3%, Fe 0.5-0.9%, Zn≤0.1%, Cu≤0.05%, Mn≤0.05%, Mg≤0.05%, V≤0.05%, and the balance is Al and other inevitable impurities, the content of each other impurity is ≤0.03%, and the total amount of other impurities is ≤0.1%.
2. A method for producing double zero aluminum foil using cast aluminum slabs, the method being used to produce the double zero aluminum foil as claimed in claim 1, It is characterized in that The following steps are included in sequence: Step 1: Melting and preparing aluminum alloy liquid according to the composition and mass percentage of double zero aluminum foil; Step 2: Use argon gas and powder refining agent to spray and refine the aluminum alloy liquid in the furnace to remove gas and impurities; Step 3: The aluminum alloy liquid flows through the degassing box and the filter box arranged on the flow trough in sequence for online degassing and filtering treatment; Step 4: Continuously casting and rolling the aluminum alloy liquid into aluminum sheet coil I under the action of ultrasonic waves; Step 5: performing the first cold rolling and high temperature annealing on the aluminum sheet coil I to obtain the aluminum sheet coil II; Step 6: cold rolling and medium-temperature annealing the aluminum sheet coil II for the second time to obtain the aluminum foil coil I; Step 7: performing a third cold rolling and low temperature annealing on the aluminum foil coil I to obtain an aluminum foil coil II; Step 8: The aluminum foil roll II is subjected to a fourth cold rolling and finished product annealing to obtain the double zero aluminum foil.
3. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The aluminum melting furnace used for smelting and preparing the aluminum alloy liquid in step 1 is a regenerative gas-fired aluminum melting furnace, and the heating melting temperature is 720-740°C.
4. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The purity of the argon gas in step 2 is ≥99.99%, the amount of the powder refining agent is 0.1-0.2% of the weight of the aluminum alloy liquid, the blowing refining time is 10-20 minutes, and the powder refining agent is composed of the following components in mass percentage: NaCl 35.12%, NaF19.84%, TiCl 3 16.51%, SrSO 4 10.06%, KPO 3 11.45%, Na 2 B 4 O 7 7.02%, the preparation method of the powder refining agent comprises the following steps in sequence: (1) selecting NaCl, NaF, TiCl with a purity of ≥99.8% according to the composition and mass percentage of the refining agent; 3 、SrSO 4 , KPO 3 、Na 2 B 4 O 7 The invention relates to a method for preparing raw materials; (2) adding the ingredients into water at a temperature of 70° C. and stirring to dissolve the ingredients into an aqueous solution, wherein the mass ratio of water to the ingredients is 1.2, and then heating the aqueous solution to 100° C. to evaporate the aqueous solution to obtain solid crystals; (3) crushing the solid crystals into powders with a particle size of less than 2 mm, and drying and dehydrating the powders at 160° C. for 4 hours to obtain the refining agent.
5. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The degassing medium introduced into the degassing box in step 3 is a mixed gas composed of argon with a purity of ≥99.99%, sulfur hexafluoride and carbon monoxide, the volume percentage of sulfur hexafluoride in the mixed gas is 9-11%, and the volume percentage of carbon monoxide is 3-5%. The rotation speed of the graphite rotor in the degassing box is 400-500 rpm, the flow rate of the mixed gas is 4-5 cubic meters / hour, and the pressure of the mixed gas is 0.2-0.3MPa.
6. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The frequency of the ultrasound in step 4 is 30-40kHz, the power of the ultrasound is 10-15kW, the temperature of the aluminum alloy liquid is 690-700°C, the casting speed is 800-900 mm / min, and the thickness of the aluminum coil I is 6-8 mm.
7. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The high temperature annealing temperature in step five is 560-570° C., the annealing time is 12-14 hours, and the thickness of the aluminum sheet coil II is 3-4 mm.
8. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The medium-temperature annealing in step six is performed at a temperature of 420-430° C., the annealing time is 10-12 hours, and the thickness of the aluminum foil roll I is 0.1-0.2 mm.
9. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The low-temperature annealing temperature in step seven is 220-230° C., the annealing time is 5-6 hours, and the thickness of the aluminum foil roll II is 0.02-0.04 mm.
10. The method for producing double zero aluminum foil using cast aluminum slab according to claim 2, It is characterized in that The finished product annealing temperature in step eight is 180-190° C., the annealing time is 3-4 hours, and the thickness of the double-zero aluminum foil is 0.005-0.009 mm.
Citation Information
Patent Citations
Method for producing ultra-wide and ultra-thin cast-rolled aluminium foil blanks by directly cast-rolling blanks with electrolytic aluminium liquid
CN102728614A
Method for producing 8111 alloy aluminum foil using cast-rolled billets
CN108300911A
Method for preparing 8079 double-zero aluminum foil blank by using electrolytic aluminum liquid
CN117089735A
Power battery aluminum foil cast-rolling blank production method and power battery aluminum foil
CN117626020A
Cited By
Aluminum alloy melt purification treatment process
CN122105173A
A process for purifying an aluminum alloy melt
CN122105173B
